THE ROLE AND IMPACT OF INTERACTIVE TEACHING METHODS IN TEACHING ENGLISH (International Conference on Scientific Research in Natural and Social Sciences, 2025)
As a result of the acceleration of the global integration process, thorough knowledge of English has become a necessity today not only in the scientific, but also in the professional sphere. Traditional language teaching approaches – techniques that emphasize memorizing grammatical rules and increasing vocabulary-often do not have sufficient effect in developing communicative competence. This article provides an in-depth analysis of the role and impact of interactive teaching methods in teaching English. It highlights the importance of engaging students in active participation through strategies such as role-playing games, "brainstorming" (storm of thoughts), keys-stadia (analysis of practical situations), and multimedia projects. Such approaches not only increase freedom and clarity of speech, but also promote critical thinking, teamwork, and cultural awareness.